2017
DOI: 10.11113/mjfas.v13n3.666
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of sulphate borophosphate glasses containing calcium oxide

Abstract: Increasing demands for better perfoming glasses have lead to current investigating of the sturctural properties of glasses for optimum performances. Calcium sulphate borophosphate glasses of different compositions were prepared using melt quenching technique. The glass forming ability and stability were checked using Differential thermal analyzer (DTA). Density and molar volume had been evaluated and analyzed. From the results of XRD, the absent of discrete and continuous sharp peaks confirmed the amorphous na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…(SBP:Ce), [32] and showed that T g , T c , and T m increased with increasing (ZSBP) [19] and glass prepared in the present study suggested that the ΔT and K H can be increased by addition of lithium. However, comparatively higher values of T g , T c , and K H have been reported for [33] [34] also showed similar trends but ΔT was comparatively low. For optical fibres, glass with higher ΔT (>100 C) are preferred to fabricate crystal-free fibre with minimal scattering loss.…”
Section: Thermal Properties Of Nd-doped Sbp Glasssupporting
confidence: 69%
See 1 more Smart Citation
“…(SBP:Ce), [32] and showed that T g , T c , and T m increased with increasing (ZSBP) [19] and glass prepared in the present study suggested that the ΔT and K H can be increased by addition of lithium. However, comparatively higher values of T g , T c , and K H have been reported for [33] [34] also showed similar trends but ΔT was comparatively low. For optical fibres, glass with higher ΔT (>100 C) are preferred to fabricate crystal-free fibre with minimal scattering loss.…”
Section: Thermal Properties Of Nd-doped Sbp Glasssupporting
confidence: 69%
“…[36] The band at 570 cm À1 was due to the bending mode of the PO 4 3À unit. [34] The bending and stretching modes of BO 4 units were observed at c. 720 and 1020 cm -1, respectively. [37] The nonexistence of the boroxol rings was reflected through the absence of a peak c. 806 cm À1 .…”
Section: Thermal Properties Of Nd-doped Sbp Glassmentioning
confidence: 95%
“…The reason for this result is that the successive increase in the content of B 2 O 3 , at the expense of P 2 O 5 , increases the number of NBOs as a result of the conversion of some Q 2 units to Q 1 ones, which was con rmed by the obtained FTIR spectra, that leads to a slight decrease in the density. This explanation is supported by the results discussed by Yamusa et al [57], who reported that the increase in the number of NBOs in the glass structure is responsible for decreasing the density of the glass samples. It should be noted that because B 2 O 3 is a network former, the density values are not always a good indicator of the packing density within the glass structure [58].…”
Section: Densitysupporting
confidence: 77%